'Workshops in healing' for senior medical students: a 5-year overview and appraisal. Issue 2 (28th January 2014) - Kearsley, John H; Lobb, Elizabeth A
Abstract : We report upon the design, content and feedback from an interactive, experiential series of Workshops in Healing for senior medical students. Fifty-six final year medical students enrolled in 2×3 h workshops designed around the core themes of 'physician know thyself' (Workshop 1) and 'confronting suffering' (Workshop 2). Of the 56 students who initially enrolled, 48 students completed both workshops and provided a written open-ended reflection of their learning experience. The study, undertaken over a consecutive 5-year period (2008–2012), employed an emergent, qualitative design using thematic analysis of the reflective comments. We found that the design and content of both workshops promoted transformative learning for these final year medical students. Students identified the following benefits: (1) the opportunity to reaffirm their commitment to their chosen career path; (2) the value of listening to other students share their stories; (3) the importance of the timing of the workshops to occur after exams; (4) the use of various mediums such as art, poetry, music and contemporary/classic literature to present concepts of suffering and healing; and (5) the creation of a safe and confidential space. Students reported that these innovative workshops gave them a renewed sense of drive and enthusiasm for their chosen career. They highlighted the importance of addressing an aspect of medicine (healing) not covered in the traditional medical curriculum. Workshops in Healing helped them to rediscover a deeper meaning to medicine and their roles as future healthcare professionals.